The JSTOR Daily Project: Building Genre Awareness through Heuristic Learning - Seeley, Sarah (Discourse and Writing/Rédactologie, 2023)
The article describes a publicly oriented writing assignment that can be adapted across disciplinary contexts. The assignment is linked to the JSTOR Daily publication with its tagline “where news meets its scholarly match.” Emulating the style of writing published in this open-access online context, students produce informative writing that contextualizes contemporary issues by drawing on applicable scholarship. As JSTOR Daily publishes a wide range of topical content, student writers can use the genre to explore a variety of topics and perspectives found across the humanities, social sciences, and sciences. This assignment can either stand-alone as a piece of web-based, potentially multi-modal, public writing, or it can be used as a starting point that supports heuristic learning as students write for this public genre then move on to write on the same topic in a scholarly genre. Teaching materials, including a sample assignment sheet and workshop prompts, are appended.